PEMANFAATAN JASA LINGKUNGAN DI HUTAN DESA BUNTOI, KECAMATAN KAHAYAN HILIR, KABUPATEN PULANG PISAU, PROVINSI KALIMANTAN TENGAH - Muhammad Zahrul Muttaqin,S.Hut,M.For.Sc,Ph.D; Ismayadi Samsoedin; Subarudi Subarudi; Nurtjahjawilasa Nurtjahjawilasa; Faridh Almuhayat Uhib Hamdani (Jurnal Analisis Kebijakan Kehutanan, 2017)
Village forest is a managed state forest by village institution for the prosperity of villagers. Village that has granted village forest is responsible for its utilization and its sustainability. The development of village forest in Buntoi Village is still at the preliminary stage; therefore the identification of environmental services, policy, institutional arrangements, and sustainable potential livelihood need to be conducted. The purpose of this study is to identify and analyse the potential of ecosystem services and influencing factors in the utilization of the ecosystem services. The result showed that there was lack of water services in the Buntoi village since there was no spring water in the forest. Also did not have the beauty of potential landscape that can attract tourists. Moreover, the potential of biodiversity and carbon sequestration in the village had not been optimised. Low utilization of ecosystem services in Buntoi was due to: (1) perceptions of stakeholders that had not yet support the utilization of ecosystem services; and (2) lack of support from district and provincial in the utilization of ecosystem services in village forest. Activities that can be developed to utilize biodiversity, beauty of landscape, and carbon conservation in Buntoi are ecotourism and REDD+ scheme.